Measurements of fast electron scaling generated by petawatt laser systems - Tanimoto, T; Habara, H; Kodama, R; Nakatsutsumi, M; Tanaka, K; Lancaster, K; Green, J; Scott, R; Sherlock, M; Norreys, P; Evans, R; Haines, MG; et al. (2009)
Fast electron energy spectra have been measured for a range of intensities between 1018 and 1021 W cm-2 and for different target materials using electron spectrometers. Several experimental campaigns were conducted on petawatt laser facilities at the Rutherford Appleton Laboratory and Osaka University, where the pulse duration was varied from 0.5 to 5 ps relevant to upcoming fast ignition integral experiments. The incident angle was also changed from normal incidence to 40° in p -polarized. The results confirm a reduction from the ponderomotive potential energy on fast electrons at the higher intensities under the wide range of different irradiation conditions. © 2009 American Institute of Physics.